A relação com o saber matemático de adolescentes em cumprimento de medida socioeducativa: sentidos e significados em um espaço privado de liberdade - Dantas, Viviane Andrade de Oliveira (2014)
The research was conducted with teenagers who are fulfilling socio educational deprivation of liberty at Centro de Atendimento ao Menor (CENAM), located in Aracaju (SE), aiming to understand how the relationship of incarcerated adolescents with mathematical knowledge is. It is observed in several studies that the discipline of mathematics is considered difficult to learn, but this knowledge is of great importance, because its use is a constant and essential requirement not only for the understanding of reality as to the construction of citizenship. This research was characterized as a guided study in the theoretical framework of the relationship with Saber (RS) as well as research on the relationship with the mathematical knowledge. Methodologically, this study enrolled in a context of a case study and has been a qualitative approach. The study subjects were internal adolescents enrolled in classrooms within this unit from 1st to 4th stage (defined as grade 1 /2 year to 4 th grade / year 5), in the form of teaching EJA - Youth and Adults. Also resorted to four (4) polyvalent teachers (one on each phase) and a pedagogical coordinator. It is noteworthy that the main subject of this research are the teenagers. For data collection we used semi-structured interviews with adolescents, the questionnaire for teachers and educational coordinator, application of balance of knowledge, analysis of the records of pedagogical supervision of adolescents and free observation. The research has shown that school for students / home is an important place for learning, even when in practice it is not observed when considering the age / grade discrepancy of these subjects. Regarding Mathematics, teenagers love this discipline, but this binding estimates, especially at the discretion of its usefulness in everyday life and the contents that represent numbers, like the four operations. This limitation of content in mathematics is understandable, as these teens did not exceed the school year as the regular age. At the same time it is interesting the relationship between recognition of mathematics, and how they use this knowledge to learn everyday situations. When we put the issue of school within a socio educational unit of deprivation of liberty, the teens relate the opportunity to leave the ALA to have a little freedom going to the classroom, they cannot have a relationship of desire in learning, performing the same tasks with dedication. There is no differentiation between the relationship of students / inmates and the mathematical knowledge within an inpatient unit compared with mathematics learned in school free of deprivation. These students continue to highlight this mathematics as a subject of greater interest in their learning, always mediating this importance with the increased possibility of applicability in everyday life.